2020
DOI: 10.1177/0193945920963800
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Food Access and Low-Income Teens: A Photovoice Approach

Abstract: Lack of access to healthy foods disproportionately impacts adolescents. This mixed-methods study used photovoice to explore everyday lived experiences of food access among teens from low-income families, empowering them to share their stories. Sixty-three diverse teens (12–17 years) from across one Midwest state took images and created narratives to support community presentations. Independent content analysis identified themes. Researchers used t tests to compare pre-post differences ( p < 0.05) for two sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 25 publications
0
30
0
Order By: Relevance
“…This consumption behavior may drive poor nutrition and unhealthy eating habits. Although some foods seem full of fat and calories, some indulgence foods are healthy and benefit health, such as dark chocolate, butter, and full-fat yogurt [ 45 ]. Indulgent behavior is an attitude of people who allow themselves whatever they want with less consideration for their wellness.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This consumption behavior may drive poor nutrition and unhealthy eating habits. Although some foods seem full of fat and calories, some indulgence foods are healthy and benefit health, such as dark chocolate, butter, and full-fat yogurt [ 45 ]. Indulgent behavior is an attitude of people who allow themselves whatever they want with less consideration for their wellness.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…The research paper found that fruit and vegetable intake was significantly related to parental modeling [ 40 ]. Parental consumption of fruit and vegetables was a predictor of their children’s fruit and vegetable intake [ 45 ]. Thus, parents impact their children’s eating behaviors as social learning is derived from observation.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…The same trend was observed with the increase in the consumption of legumes and dairy and decrease in the consumption of starchy vegetables and SSBs, in which the 14-18 age group had a higher variation between the national diet and optimized diet than the other two food groups. This is understandable, as teenagers tend to spend more time outside of the house, where choices including unhealthy diets are highly prevalent [49].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in one study, Simpson and colleagues applied the photovoice technique to investigate the lived difficulties of healthy food access by low-income teens across six counties. 17 The teens were instructed to depict food access, intake, and the local environment through a minimum of 10 photos taken over a two-week period. During the data collection process, the teens selected three images to "tell a story" using the SHOWeD structured dialogue technique.…”
Section: Nursing Research Step By Stepmentioning
confidence: 99%
“…The photographic data are then analyzed through critical dialogue with the study participants. For example, in one study, Simpson and colleagues applied the photovoice technique to investigate the lived difficulties of healthy food access by low-income teens across six counties 17. The teens were instructed to depict food access, intake, and the local environment through a minimum of 10 photos taken over a two-week period.…”
Section: Qualitative Data Collectionmentioning
confidence: 99%